2011
DOI: 10.19030/jber.v9i4.4209
|View full text |Cite
|
Sign up to set email alerts
|

Applying Six Sigma To Achieve Enterprise Sustainability: Preparations And Aftermath Of Six Sigma Projects

Abstract: Sustainability is not a method or a tool; it is the state of a company in which the efficiency of resources is maximized, customers are satisfied to a great extent, an improved condition is long-lasting, success is maintained and competitive advantage is sustained. Literature review carried out in this research depicts that researchers have extensively worked on identifying and documenting the enablers, challenges, risks, projects, corporate commitments and strategic integration of Six Sigma with other framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…and direct the organization towards innovation(AlSagheer, 2011). In addition,Zu et al (2010) have found that both group and rational types of culture may facilitate top management's commitment in organizations.…”
mentioning
confidence: 99%
“…and direct the organization towards innovation(AlSagheer, 2011). In addition,Zu et al (2010) have found that both group and rational types of culture may facilitate top management's commitment in organizations.…”
mentioning
confidence: 99%